Pengaruh Level Substitusi Rumput Bothriochloa pertusa dengan Kangkung Terhadap Tingkah Laku Makan Ternak Kambing Kacang - Marselinus Ranboki; Gustaf Oematan; I Gusti Ngurah Jelantik (Animal Agricultura, 2023)
The aim of this experiment was to determine the effect of level of substitution of Bothriochloa pertusa grass with water spinach on the feeding behavior of kacang goats. As many as 4 kacang goats, ranging in age from 1-1.5 years with an initial body weight of 16,2 – 19,8 kg averaged ± 18 kg were involved in this experiment. This study followed the Latin Square Design (RBSL) 4 x 4 with 4 treatments and 4 periods as replications. The treatments were P0: 60% Bothriochloa pertusa grass + 40% leucaena, P1: 45% Bothriochloa pertusa grass + 40% lamtoro + 15% water spinach, P2 : 30% Bothriochloa pertusa grass + 40% leucaena + 30% water spinach , P3: 15% Bothriochloa pertusa grass + 40% leucaena + 45% water spinach. The measured variables included the frequency and eating time, frequency and ruminating time, and frequency and resting time. The data obtained were analyzed using Analysis of Variance (ANOVA). Replacing Bothriochloa pertusa grass with water spinach is expected to reduce the lenght of eating of kacang goats The results showed that treatment had no significant effect (P>0,05) on the measured parameters. The duration and frequency of feeding ranged from 7.3 to 8.5 hours and 9.75 to 10.12 times per day, duration and frequency of rumination ranged from 6.7 to 7.18 hours and 10.12 hours to 10.50 times per day, and the length and frequency of rest ranged from 8.27 to 9.15 hours, and 16.37 to 18.62 times per day. It was concluded that the substitution of Bothriochloa pertusa grass with water spinach does not affect on the ingestive behavior of kacang goats.